Prayer and Islamic Da’wah(Speech) Therapy in Reducing Thestudents’ Traumaafter Earthquake in SMA NW Perian - M. DeniSiregar; Syukri; Abdul Halim Rahmatullah (Simposium Antar Bangsa Seminar dan Workshop)
Earthquake which shook Lombok island with M = 7.0 on August 5, 2018 caused trauma to victims who kept feeling fear aftershocks. Besides, they were also overwhelmed by panic and anxiety, and this even led to stress due to loss of family and property. Thousands of important homes and facilities were destroyed at the location of the earthquake epicenter. Lombok people, especially school children, are very anxious and uneasy so that they still tell a deep sadness. Islamic prayer and da'wah therapy activities are held at NW High School Perianto heal students who experienced things like the symptoms stated previously, so in this way they can increase their memory and have high awareness in facing the problems. Students are now beginning to be able to emit all emotions and pass it on to everyone in order to get attention of others; they begin to be able to enter classes from the 1st to 3rd floor. They are able to strengthen and motivate each other among students in the school even in the community dealing with the problems. They always worship and continue to get closer to Allah SubhanahuWaTa’ala, and they are no longer worried because all of them believe that a good deed will get a good reward. They now always put their trust in God.